Desempenho reprodutivo de fêmeas bovinas de corte no primeiro e segundo ano de acasalamento - Pacheco, Rangel Fernandes (2016)
The objective of this work was to evaluate the reproductive performance of beef heifers in the first and second reproductive year. Two hundred twenty- seven heifers mated for the first time at 24 months old, which reached the minimum live weight of 50% of the adult weight, and were mated from 2003 to 2012 and raised at the Beef Cattle Laboratory (LBC) of the Animal Science Department of Federal University of Santa Maria (UFSM) were studied. In chapter 1, each variable was evaluated through logistic regression, by the LOGISTIC procedure available at SAS. The explanation for the pregnancy rate (58.1%) in the first reproductive year was the intensity of the weight gain from 7 to 18 months old and from 18 to 24 months old. In the second reproductive year, the pregnancy rate of the primiparae (49.5%) was explained by the variation on the weight of the heifers from the age of 24 months old to the birth; by the Julian date of birth; by the average daily gain from the weaning to the end of the breeding season and by the adjusted weight of the calf at weaning (75 days). In chapter 2, the heifers were grouped in three classes of live weight at 24 months old, being them: between 50 and 59.9% of adult weight (55%); from 60 to 69.9% of adult weight (65%) and between 70 and 80% of adult weight (75%). The performance of the heifers was monitored from 7 months old until the end of the second breeding. The pregnancy rate in the first reproductive year was 38.0%; 56.4% and 69.0% for the heifers mated with the weight range of 55% 65% and 75%, respectively. The weight difference between 24 months old and the birth was superior (P<0.05) on the classes of 55% (37.8 kg) and 65% (24.5 kg) compared to the class of 75% (-7.9 kg). The pregnancy repetition rate did not suffer effect of the weight class at the first mating (P>0.05) with values of 41.6%; 42.1% and 50.4%. When the mating weight of the heifers is not a limiting factor, the weight gain intensity between 7 and 24 months old is the main factor that influences on the pregnancy rates. In the second reproductive year, higher weight increments along the period of mating and gestation, as well as the reduction of the birth date and an increase on the weight gain intensity in post weaning are necessary in order to increase the pregnancy repetition indexes. The increase of weight before the mating of the heifers at two years old influences on the reproductive performance at the first breeding; promotes higher weight at birth, weaning and at the end of the second breeding in relation to the heifers mated between 50% and 60% of the adult weight, however it results in a higher assistance in the second reproductive year due to the higher corporal development.